A Literature-Based Perspective on Human-Centered Design and Evaluation of Interfaces for Virtual Reality in Robotics - Hao, Chenxu; Dwivedi, Anany; Beckerle, Philipp (Springer Proceedings in Advanced Robotics, 2023)
Over the past decade, the use of virtual reality applications is increasing in the field of robotics, which is set to increase even further with the advent of “Metaverse”. Metaverse is considered as an “embodied internet” which will seamlessly integrate machines, robots, and computer applications including those in virtual and augmented reality. In this work, we review the current state of research and discuss the underlying problems with the current design and evaluation methods for the state-of-the-art virtual reality interfaces employed in the field of robotics. To overcome these issues, we present our perspective on the methods for design and evaluation of such interfaces. Our perspective takes into account human-centered design methods along with the functional measures of evaluating the performance of the interfaces. This interdisciplinary perspective emphasizes rigorously designed empirical experiments that require close collaborations among engineers, designers, human-computer interaction researchers and cognitive scientists.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Augmented reality; Human-machine interfaces; Human-robot interaction; Virtual reality